The Importance of Sex Stratification in Autoimmune Disease Biomarker Research: A Systematic Review - Purnamawati, Kristy; Ong, Jamie Ann-Hui; Deshpande, Siddharth; Tan, Warren Kok-Yong; Masurkar, Nihar; Low, Jackson Kwee; Drum, Chester Lee (Frontiers in Immunology, 2018)
The immune system is highly dynamic and regulated by many baseline characteristic factors. As such, significant variability may exist among different patient groups suffering from the same autoimmune disease (AD). However, contemporary research practices tend to take the reductionist aggregate approach as they do not segment the AD patients before embarking on a biomarker discovery-phase. This approach has been productive: many novel AD biomarkers have recently been discovered. Yet the subsequent validation studies of these biomarkers tend to suffer from a lack of specificity, sensitivity, and reproducibility which may hamper their translation for clinical use. To enhance reproducibility in validation studies, an optimal discovery-phase study design is paramount: one which takes into account the different parameters affecting the immune system biology. In this systematic review, we highlight the need for stratification in one such parameter, i.e. sex stratification. We will first explore sex-differences in the immune system biology and AD prevalence, followed by a summary of sex-bias in the clinical phenotypes of two ADs: one which more commonly affects females: systemic lupus erythematosus, and one which more commonly affects males: ankylosing spondylitis. The practice of sex stratification in biomarker research may not only advance the discovery of sex-specific AD biomarkers but more importantly, promote reproducibility in subsequent validation studies, thus easing the translation of these novel biomarkers from bench to bedside to improve AD diagnosis. In addition, such a practice will also provide insights into the differential underlying AD pathology in males and females, which will be useful for the development of more effective interventions for each sex type.